(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2017)
The traditional architecture is the cultural identity of a tribe because they have life of its people. Traditional architecture experiencing growth and renewal. Renewal of the traditional architecture of Makassar happens usually get influences from the outside architecture that fit into the traditional architecture thus experiencing blend elements of culture, but the culture of the traditional architecture of original tribes of Makassar maintain, this is called acculturation. Acculturation is a blend of one cultural and the other retaining local indigenous culture. The traditional architecture is experiencing a mix of cultures occurs in public housing environment is an element of the macro, mezo and micro. Incessant development in various sectors particularly the sectors of housing and settlement, this is what happen in the settlement processing brick Gowa district, where the development of the construction of the society processor brick has provoked aspects psychology, than it is that it raises the problem is how the role of ideal form of architecture Makassar who have undergone traditional blend of cultures can form needs humanist residential environment that is safe, convenient, and economic, hygienic. The purpose of this study was to analyze element the of original culture at traditional Makassar particularly in ideal form home to work place primary and support in shaping the residential environment humanist. This research is a descriptive exploratory and interpretative studied theoretically by means observe directly the ideal form of settlement processing bricks in Gowa of South Sulawesi. The results of this study indicate the ideal form of settlement processing in the hamlet brick- Giring-Giring Village Kalase’rena Bontonompo Gowa District of review the system orientation of the house, the tread pattern of at macro space occupancy humanist element appear in the system path, distance, direction of the wind , the working group, the increase in the economic, social and hierarchy family indicates comfort, security, economic to the location of key livelihood source and support to the community house brick processing.